Membangun Budaya Organisasi yang Inklusif : Strategi untuk Meningkatkan Kinerja dan Kepuasan Karyawan - Hasibuan, Suaib; Hasibuan, Wildan Anshori; Hasibuan, M. Zaidan Ghanim; Yakub, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article aims to explore strategies for building an inclusive organizational culture to enhance employee performance and satisfaction. The research employs a qualitative literature study approach, analyzing various theories and previous studies related to inclusive organizational culture and its implications for employee motivation and productivity. The findings suggest that an inclusive organizational culture fosters a more open work environment, enhances mutual respect, and strengthens interpersonal relationships among employees. Furthermore, an inclusive culture contributes to individual skill development, innovation, and better team performance. This study provides insights into the importance of integrating inclusive values in human resource management to achieve organizational goals.